2001
DOI: 10.1002/dvdy.1131
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐calcium exchanger (NCX‐1) and calcium modulation: NCX protein expression patterns and regulation of early heart development

Abstract: Ouabain-induced inhibition of early heart development indicated that Na/K-ATPase plays an important role in maintaining normal ionic balances during differentiation of cardiomyocytes (Linask and Gui [1995] In order to identify a connection between heart development and NCX-mediated Ca ؉؉ regulation, we determined the embryonic spatiotemporal protein expression pattern of NCX-1 during early developmental stages. In both chick and mouse embryos, NCX-1 (the cardiac NCX isoform) is asymmetrically expressed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…In particular, NCX1 expression is highly restricted to the early embryonic heart and serves an important role in heart development (Koushik et al, 1999;Linask et al, 2001). Moreover, high levels of NCX1 expression and Na + /Ca 2+ exchange activities have also been found in other tissues, such as brain and kidney (reviewed in Friedman, 1998;Sakaue et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, NCX1 expression is highly restricted to the early embryonic heart and serves an important role in heart development (Koushik et al, 1999;Linask et al, 2001). Moreover, high levels of NCX1 expression and Na + /Ca 2+ exchange activities have also been found in other tissues, such as brain and kidney (reviewed in Friedman, 1998;Sakaue et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the Na=K-ATPase, that is, the sodium pump, plays an important role in maintaining normal ionic balances during differentiation of cardiomyocytes [5]. Inhibition of the sodium pump is generally accepted to affect the activity of the Na-Ca exchanger 1; we and others provided evidence that the Na-Ca exchanger 1 drives the initial embryonic heartbeats, as well as disrupts normal myofibrillogenesis [6,7]. A close association appears to exist during cardiomyocyte differentiation among Ca fluxes, differentiation of the contractile apparatus, and maintenance of ionic balances.…”
Section: Stem Cells and Developmentmentioning
confidence: 93%
“…In addition, when embryos were treated with a Ca 2+ buffer, BAPTA, one of the most obvious effects was the development of a defective heart; even though a distinct atrium and ventricle were still formed, the heart was smaller than normal and was not capable of pumping blood (Créton et al, 1998). In the chick, when embryos were treated with ouabain or ionomycin to increase the intracellular Ca 2+ either indirectly (via the NCX) or directly, respectively, differentiation of the cells in the posterior areas of the heart-forming region was blocked (Linask et al, 2001). In addition, treatment with KB-R7943, an NCX inhibitor, affected the early development of the heart and blocked the initial heart beats in the chick embryo (Linask et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the chick, when embryos were treated with ouabain or ionomycin to increase the intracellular Ca 2+ either indirectly (via the NCX) or directly, respectively, differentiation of the cells in the posterior areas of the heart-forming region was blocked (Linask et al, 2001). In addition, treatment with KB-R7943, an NCX inhibitor, affected the early development of the heart and blocked the initial heart beats in the chick embryo (Linask et al, 2001). Ca 2+ signaling also plays a key role in heart development in mammals.…”
Section: Introductionmentioning
confidence: 99%